2014
DOI: 10.3389/fnhum.2014.00302
|View full text |Cite
|
Sign up to set email alerts
|

An aberrant precision account of autism

Abstract: Autism is a neurodevelopmental disorder characterized by problems with social-communication, restricted interests and repetitive behavior. A recent and thought-provoking article presented a normative explanation for the perceptual symptoms of autism in terms of a failure of Bayesian inference (Pellicano and Burr, 2012). In response, we suggested that when Bayesian inference is grounded in its neural instantiation—namely, predictive coding—many features of autistic perception can be attributed to aberrant preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

56
598
5
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 529 publications
(713 citation statements)
references
References 105 publications
56
598
5
3
Order By: Relevance
“…Importantly, the current findings provide direct support for recent proposals suggesting that failures in Bayesian inference, and particularly aberrant precision (i.e., inverse variance) of the information encoded at various levels of sensorimotor hierarchies, may contribute to socio-emotional deficits in ASD (Friston, et al, 2013b; Lawson, et al, 2014; Pellicano and Burr, 2012). Specifically, abnormally high interoceptive precision (i.e., over reliance on ascending interoceptive information), in the context of interoceptive inference, would result in hypersensitivity of principal AIC neurons that provide downstream predictions of interoceptive signals (Friston, 2010; Seth, et al, 2011).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Importantly, the current findings provide direct support for recent proposals suggesting that failures in Bayesian inference, and particularly aberrant precision (i.e., inverse variance) of the information encoded at various levels of sensorimotor hierarchies, may contribute to socio-emotional deficits in ASD (Friston, et al, 2013b; Lawson, et al, 2014; Pellicano and Burr, 2012). Specifically, abnormally high interoceptive precision (i.e., over reliance on ascending interoceptive information), in the context of interoceptive inference, would result in hypersensitivity of principal AIC neurons that provide downstream predictions of interoceptive signals (Friston, 2010; Seth, et al, 2011).…”
Section: Discussionsupporting
confidence: 84%
“…Physiologically, this precision or attention is thought to be mediated by the postsynaptic gain or sensitivity of neuronal populations reporting prediction error (Bastos, et al, 2012). The specific failure in ASD has been attributed to a relative increase in the precision of sensory evidence and over the precision of higher (extrasensory) beliefs (Friston, et al, 2013b; Lawson, et al, 2014; Pellicano and Burr, 2012; Quattrocki and Friston, 2014; Van de Cruys, et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Pellicano & Burr (2012) proposed that the use of priors in persons with ASD is attenuated relative to typically developing people and therefore the active process of 4 formulating and testing hypotheses about the world is more immune to suggestion, which results in a tendency to perceive the world more objectively, and a desire to be in more familiar settings. Similar accounts have been developed over the last few years by other researchers (e.g., Davis & Plaisted-Grant, 2015;Lawson, Rees, & Friston, 2014;van Boxtel & Lu, 2013;Van de Cruys et al, 2014).…”
Section: Introductionsupporting
confidence: 69%
“…Interestingly, it has recently been suggested that increased visual responsiveness to low‐level features, as reported in this study, may arise due to a larger noise in the primary visual system (Simmons et al, 2009; Lawson, Rees, & Friston, 2014). Along those lines, a larger intra‐individual variability of the evoked visual response has been reported in ASD (Dinstein et al, 2012; Haigh, Heeger, Dinstein, Minshew, & Behrmann, 2015).…”
Section: Discussionmentioning
confidence: 49%